The Family Hope Program For Conditional Cash Transfer Programmed: Case Depok City - Chotim, Erna Ermawati; Tedja, Jeanne Noveline (Journal Research of Social Science, Economics, and Management, 2022)
As an effort to accelerate poverty alleviation, since 2007 the Government of Indonesia has implemented PKH. The Social Protection Program, which is also known internationally as Conditional Cash Transfers (CCT), has proven to be quite successful in overcoming the poverty faced in these countries, especially the problem of chronic poverty. However, as a conditional social assistance program, PKH has not made it easy for poor families, especially pregnant women and children, to take advantage of the various health service facilities and educational service facilities, available around them. The benefits of PKH have also begun to be encouraged to cover persons with disabilities and the elderly by maintaining their level of social welfare in accordance with the mandate of the constitution and the Nawacita of the President of the Republic of Indonesia. This method uses a qualitative approach using relevant informants. The results of the study showed that there were still findings of PKH maladministration by public service supervisory agencies because socialization was not optimal. Second, there is still inaccurate recipient data so there are still families who are eligible to receive PKH assistance but do not receive it. On the other hand, families who are not eligible receive assistance. Apart from the social development strategy by the individual, there are other strategies such as the social development strategy by the community. In addition, this PKH strategy focuses on community development and social development, then there is also community action, participation, and social development. Furthermore, there is a social development strategy by the government that focuses on promoting social development through integrated planning.